Orthodontic treatment during pregnancy, lactation, and postmenopausal period: a questionnaire development - Juliana de Lourdes FERNANDES; Matheus França PERAZZO; Saul Martins PAIVA; Paulo Antônio MARTINS-JÚNIOR; Soraia MACARI (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study aimed to develop and validate a self-administered questionnaire in Brazilian Portuguese to verify the level of knowledge of orthodontists in the care of pregnant, lactating, and postmenopausal women, named "Considerations on Orthodontic Treatment during Pregnancy, Lactation, and Postmenopausal Periods." The development and validation of the questionnaire consisted of the following steps: a) item generation; b) item reduction; c) questionnaire design; and d) validity and reliability tests in a cross-sectional study with 258 orthodontists working in the field from different Brazilian states. A total of 60 orthodontists participated in test-retest over a mean period of 45 days. The preliminary questionnaire consisted of a total of 60 questions. After item reduction, 40 questions were selected for the final version of the questionnaire, with eight questions about pregnant women; six about lactating women; 18 about postmenopausal women, and eight about general knowledge in dentistry. Each item had three response options in the Likert scale format. Face and content validity analysis, reliability assessment through internal consistency (Cronbach's alpha and McDonald's omega), and test-retest reliability through the intraclass correlation coefficient (ICC) and Spearman's correlation coefficient were performed. Face and content validity indicated that the questionnaire was considered valid, objective, and easily understandable. The questionnaire had good internal consistency (Cronbach's alpha = 0.77; McDonald's omega = 0.78) and good test-retest reliability (ICC = 0.71; Spearman's correlation coefficient = 0.51). The questionnaire was considered valid and reliable to assess the level of knowledge of orthodontists in the care of pregnant, lactating, and postmenopausal women.